DOCUMENT AUTHENTICATION USING BLOCKCHAIN: DIPLOMA VALIDATION AS A TEST CASE - Makarenko, Natalya (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Blockchain technology consists of a decentralized digital ledger of transactions that provides an assurance of data immutability when properly implemented. The promise and premise for transactional systems that incorporate blockchain is that they are inherently more trustworthy than prior solutions. The attributes of security and transactional transparency have contributed to the rapid integration of blockchain across a broad spectrum of routine digital engagement with government, healthcare, and commerce. The European Commission describes blockchain as the digital future of Europe, and is currently implementing the European Blockchain Services Infrastructure (EBSI) project, which will cover 27 countries and will include, among other things, the management of educational credentials. This thesis examines the potential applicability of blockchain in the context of formal document authentication, using the field of education as the demonstration case. The issuance and validation of academic documents such as diplomas, certificates, and transcripts can be carried out on the basis of the blockchain, which would enable reliable automation of the processes related to verification of document authenticity in circumstances such as background checks, employment screenings, and compliance with the Apostille Convention on the certification of international documents. In this work I examine the recommended standards, including the W3C Verifiable Credentials, W3C Decentralized Identifiers, EBSI Verifiable Credentials and the possibility of using the peer-to-peer InterPlanetary File System (IPFS). I also examine the methodologies for implementation, including mechanisms for verification and revocation. On this basis, I designed and tested two implementations to demonstrate proof-of-concept. The first is based on Blockcerts, which is a kind of turn-key approach. It is more cost-efficient, allowing batch issuance of diplomas (up to 2000 diplomas in one transaction). The second uses Smart Contracts on the Ethereum platform and more expensive, but more promising in terms of the volume of tasks that can be solved on its basis. The results showed that both approaches can be successfully applied for the needs of the university and implemented (both on a public and private blockchain network). All technical notes on the use of Blockcerts, including Time and Cost tests and deployment strategies of both approaches have been included in the Appendix, as a model for potential deployment.
Keywords: type of access: gated access; Research Subject Categories::TECHNOLOGY; blockchain; Inter Planetary File System; EPSI; European Blockchain Services Infrastructure; EBSI